Inviting Politics to Dinner: An Ecofeminist Analysis of Meat Eating - Abromaitis, Susanne (Tufts Archival Research Center, 2019)
Summary: Food is a constant presence in our lives, serving many functions: sustenance, social facilitation, comfort, among others. Yet very little research has been done examining the motivations involved in food choice from a sociopolitical context.; Final Project: February 2001.; Advisors: Dr. Elizabeth Lawrence, Dr. Marion Copeland.; Thesis submitted for the MS in Animals and Public Policy degree.